Casca de mamona em dietas para ovinos de corte - Beserra, Liandro Torres (2010)
The objective of this study was to evaluate four substitution levels (0, 33, 67 and 100%) of Tifton 85 hay by castor hulls on the diet of Morada Nova, males, non-castrated, crossbred sheep on average aged 7 months and weighting 20.3 kg so that it was possible to compare bioeconomic performance of each diet. The experimental design was established with four treatments and five repetitions. It has been used a 50% ratio between roughage and concentrated feed. Confinement lasted 70 days: 14 days of adaptation and 56 of data collection. It has been observed reductions on both progressive intake nutrient and animal performance, however, from 67% substitution level on, biological performance has dropped drastically. Increasing the percentage of substitution level has not resulted in significant changes on feedlot sheep behavioral characteristics. It has been observed both higher food and rumination efficiency with lower levels of castor hulls and also differences between on morphometric measures: body weight (PC), body weight at slaughter (PVA), empty body weight (PCV), hot carcass weight (PCQ), cold carcass weight (PCF) and empty body performance (RCV). Analyses on cut weights made on the carcass have presented differences on: half carcass, leg, loin back, shoulder, flank and neck. Concerning cut economic returns, leg and loin cuts later have presented differences between different substitution levels and regarding on non-carcass treatments, it has been observed economic differences for skin, head, feet, trachea/ lung/ tongue, diaphragm, heart, liver, spleen, kidney, omasum, rumen/ reticulum and for perirenal fat. Concerning to nutrients, 0-33% substitution level has presented best results followed by 67% substitution level, which has presented intermediate values, and 100% substitution level, with the worst results. Finally, it has been made technical, zootechnical and economical analysis based on both costs of each diet and dry matter (MS) consumption. Daily production (kg / PV) and productivity (kg / day x sheep) have been higher in production systems with smaller amount of castor hulls on the diet due to the higher consumption of dry matter (MS) which has resulted in: increased animal performance; higher number of animals with ideal weight to be slaughtered per year; and in higher gross income kg/ PV (R$/ month). On the other hand, total cost (R$/ month) decreases while increasing substitution levels, mainly because of the low prices of castor hulls. Results pointed on drastically feed decreasing costs on systems with higher castor hulls. 67% substitution level have presented the highest liquid income per year (R$ 4,600.00); a 1.04 cost-benefits relation; a 23% internal return rate (TIR); and a Liquid Present Value (VPL) of R$ 22,888.97.